2015
DOI: 10.1002/alr.21645
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal orbital cavernous hemangioma resection: global experience in techniques and outcomes

Abstract: Extraconal lesions were managed similarly; however, greater variability was evident for intraconal lesions. These included the laterality and number of hands in the approach, methods of medial rectus retraction, and the need for reconstruction. The increased technical complexity and disparity of techniques in addressing intraconal OCHs suggests that continued research into the optimal management of this subclass of lesions is of significant priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 19 publications
5
112
0
1
Order By: Relevance
“…Total resection of the tumor was achieved in 16 cases; in the remaining 7 cases, partial tumor resection, orbital decompression, and/or optic nerve decompression were conducted. Bleier et al reported that tumors inside the muscle cone can still be resected transnasally, but that such resections are limited to tumors located on the medial side of the optic nerve . However, their rate of total resections was significantly reduced compared with the rate for tumors located outside of the muscle cone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total resection of the tumor was achieved in 16 cases; in the remaining 7 cases, partial tumor resection, orbital decompression, and/or optic nerve decompression were conducted. Bleier et al reported that tumors inside the muscle cone can still be resected transnasally, but that such resections are limited to tumors located on the medial side of the optic nerve . However, their rate of total resections was significantly reduced compared with the rate for tumors located outside of the muscle cone.…”
Section: Discussionmentioning
confidence: 99%
“…However, compressing and pulling the sutures that encircle the muscles poses a risk of injury to the oculomotor nerve and the ophthalmic artery. Bleier et al pointed out that the use of blunt probes to intermittently move the muscles through the nasal septum window can maximize protection of the peripheral nerve and vascular supply . Exposure of the tumor by treating the orbital fat using bipolar electrocoagulation is still controversial, as it may damage the medial and inferior branches of the ophthalmic artery and oculomotor nerve that feed the medial rectus muscle .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of data has been acquired by retrospective case reports and case series. The highest LOE has been provided by 2 systematic reviews as well as 2 multicenter retrospective review studies …”
Section: Optic Nerve and Orbitmentioning
confidence: 99%
“…OCH, being the most common adult orbital tumor and having a dense fibrous capsule to facilitate dissection, represents the ideal index lesion for study. Despite a recent global outcomes study specifically focusing on OCH, the literature on endonasal orbital tumor surgery is still quite heterogeneous due to the complexity of the intraorbital anatomy and varying relationship of the tumor to critical neurovascular structures and skull‐base foramina. In an effort to standardize the reporting of outcomes, an international, anatomic‐based staging system was developed for endonasally resectable OCH.…”
mentioning
confidence: 99%